Cape Verde : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper examines macroeconomic challenges for a highly tourism-based economy such as Cape Verde. The changing structure of Cape Verde's balance-of-payments financing calls for a closer look at the volatility of remittances and their role as an absorber of economic shocks. The paper finds that compared with other external inflows, remittances continue to be a reliable source of foreign financing, but they are declining in importance. It also shows that this influence seems to be gradually fading, and remittances are becoming increasingly procyclical.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Cape Verde Exchange Rate Regime; CR; Growth Cycle; ISCR; Years Remittance